Penerapan Metode Tandur dan Melempar “Bola Salju” (T & BS) untuk Meningkatkan Hasil Belajar pada Siswa SDN 8 Jenggik - Suhaili Munahar (PALAPA, 2016)
This study aims to improve student learning outcomes SDN 8 Jenggik through the application of methods of T & BS. Based on observations and interviews with teachers of grades there are some problems at the time of learning as the low student learning, lack of attention to students' learning process. To overcome the existing problems teachers should improve the system of learning one way to apply the method Tandur and throws a "Snowball" (T & BS). The subjects were students of class IV SDN 8 Jenggikyang totaling 24 people. based on the observation of the activity of students in the first cycle obtained a score of 44 in the category of active, while the second cycle obtain a score of 48 in the category are very active. And for learning management in the first cycle at 13 with good category, while in the second cycle which was 17 in the category very well. For the average value in the first cycle of students is 73.19 to 77.09 in the second cycle. So the 4-digit increases while the completeness of classical study by KKM set is > 70. In the first cycle of 68.18% and the second cycle be 82.60% which increased 14 digits.